T.I.M.E.R.S. for foot ulcers – current management strategy - Furga, Artur; Dalkowska, Barbara; Dzięgielewski, Jędrzej; Barczak, Iga (Nursing Problems / Problemy Pielęgniarstwa, 2024)
Managing venous ulcers poses significant challenges for nursing personnel. This article outlines the current strategies employed in addressing venous ulcers, with particular emphasis on the updated T.I.M.E.R.S. wound assessment tool and compression therapy. Diagnosis should consider risk factors associated with chronic venous disease as well as other conditions such arterial ischaemia, ulcers related to diabetic neuropathy, or cancer. Doppler duplex ultrasound is typically conducted to validate the diagnosis. In the treatment of chronic wounds, implementing the updated wound assessment strategy T.I.M.E.R.S. is recommended. Optimal wound management requires tailored dressings and usage of antimicrobial agents. Application of local antibiotics on wounds should be avoided, with the exception of gentamicin embedded in a collagen matrix presented in the form of a sponge. Correctly adjusted com-pression therapy is a gold standard of treatment. Pentoxifylline is advised as an oral treatment to expedite the rate of ulcer healing.